2015
DOI: 10.1002/jsfa.7477
|View full text |Cite
|
Sign up to set email alerts
|

In ovo administration of copper nanoparticles and copper sulfate positively influences chicken performance

Abstract: The in ovo application of Cu colloids may ensure an efficient penetration of Cu into the embryonic tissue with long lasting effects on postnatal growth. The method may provide a successful alternative to using Cu as a feed additive. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…There was a significant improvement in feed efficiency with zinc (2.16), copper (2.46) and selenium (2.51), when 40 µg, 4 µg, and 0.225 µg per egg respectively were used via in ovo administration . In ovo administered copper has been reported to be better utilized and less excreted than when fed post‐hatching to chicks . Thus, this route of administration when used for mineral and vitamin supplementations can prove to be cost effective in poultry production.…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant improvement in feed efficiency with zinc (2.16), copper (2.46) and selenium (2.51), when 40 µg, 4 µg, and 0.225 µg per egg respectively were used via in ovo administration . In ovo administered copper has been reported to be better utilized and less excreted than when fed post‐hatching to chicks . Thus, this route of administration when used for mineral and vitamin supplementations can prove to be cost effective in poultry production.…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%
“…94 In ovo administered copper has been reported to be better utilized and less excreted than when fed post-hatching to chicks. 95 Thus, this route of administration when used for mineral and vitamin supplementations can prove to be cost effective in poultry production. In addition, in ovo supplementation of trace element (zinc, selenium, or iodine) did not affect post-hatch growth.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…In our experiment on young turkeys, the dietary supplementation with Cu-NP, in particular at the inclusion level of 20 mg/kg, decreased plasma glucose concentrations in turkeys (Kozłowski et al, 2018). Mroczek-Sosnowska et al (2016) also observed a decrease in plasma glucose levels of chickens administered Cu-NP in ovo during embryogenesis. However, in the present study, the above effects were not confirmed when Cu-SUL was replaced with Cu-NP and when the dose of supplemental Cu was decreased.…”
Section: Discussionmentioning
confidence: 66%
“…In a different study utilizing a chick embryo model, CuNP exposure resulted in marked proangiogenic and proliferative effect via the upregulation of VEGF and other angiogenic factors (81;82). It is noteworthy that modulation of VEGF signaling is a recurring theme in the antiangiogenic effects of metallic ENM.…”
Section: Examples Of Enm Vascular Toxicitymentioning
confidence: 99%